Reflexões linguísticas produzidas por crianças em suas atividades metalinguísticas - Dias, Rosângela Hanel (2018)
The field of studies on the teaching of Portuguese in the early years of elementary school, despite the amount of research that accumulates, still lacks work on grammar teaching. The present research was aimed at the linguistic reflections formulated by fourth year elementary school children, when they were asked to handle concepts from the field of syntax, which were problematized in the course of a Didactic Sequence to Learn Grammar (CAMPS, 2000). Among their objectives is to understand children's reflections about language, their interaction with their peers and adults, and the links they produce between the previous knowledge and the linguistic knowledge provided by the teacher, in the course of a proposal of didactic organization formulated and executed with a view to triggering and potentializing metalinguistic reflections and practices of systematization of linguistic knowledge by the students. The research was guided by the principles of the qualitative approach, benefiting from methodological elements of the collaborative research. Researcher and teacher developed a didactic sequence to learn to write (DICKEL et al., 2016) and, as part of it, a Didactic Sequence to Learn Grammar - SDG, didactic modality proposed by GREAL - Research Group on Teaching and Learning of Languages (Universität Autònoma de Barcelona) for the teaching of language (s), together with a 4th year elementary school of a private school in the municipality of Passo Fundo. The observation was documented through video recordings, photographs, children's written records and field diary. The analysis of the data is based on the categories of metalinguistic activity, proposed by Camps (2000), and the sociodiscursive approach of the language, especially from the productions of Mikhail Bakhtin. The results indicate that the movement to construct the children's linguistic reflections is oriented, mainly, by semantic criteria, through which they seek to assign relations of meaning to justify the functioning of the language. In addition, the activities of metalinguistic reflection proposed by the SDG favor the taking of the language as object of study, benefited by the metalanguage offered by the instruction provided by the teacher. The theoretical knowledge regarding the functioning of the language is a fundamental condition for the teacher so that he can problematize the elaborations of the children and promote more complex levels of approximation between these subjects and the possibilities of this cultural tool.